Didactics of creative writing - Montilla Narváez, Raxson (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
This article aims to define a didactics of creative writing based on the epistemic conceptualization of general didactics and the delimitation of its object of study. Understanding that teaching creative writing requires the educator to become an active agent, to know the literature, the written production processes and the formal rules of the language. Furthermore, as a creative process, it allows the development of the student’s thinking, an active and autonomous subject that builds and contributes to their learning, one that transcends the formulas of production, encouraging the development of their own voice and representing the territory.